Age and gender differences in the association between body mass index and all-cause mortality among older Japanese. Issue 6 (17th August 2020) - Murayama, Hiroshi; Liang, Jersey; Shaw, Benjamin A.; Botoseneanu, Anda; Kobayashi, Erika; Fukaya, Taro; Shinkai, Shoji
ABSTRACT : Objective: Increasing evidence suggests a reverse J-shaped association between body mass index (BMI) and all-cause mortality among the older population. However, findings from non-Western societies including Japan are still sparse. Furthermore, little evidence regarding variation by age and gender in the BMI-mortality relationship in old age exists. This study aimed to examine age and gender variations in the relationship between BMI and all-cause mortality among older Japanese. Design: Data came from a national representative sample of community-dwelling Japanese aged 60 years and older at baseline ( n  = 4, 869). Participants were followed for up to 25 years. We categorized BMI into seven categories: < 18.5, 18.5–19.9, 20.0–21.4, 21.5–22.9, 23.0–24.9, 25.0–26.9, and ≥ 27.0. Cox proportional hazards models were used to assess the relative mortality risk associated with BMI categories. Results: Lower BMI (< 18.5 and 18.5–19.9) was associated with higher mortality, compared to the mid-normal weight category (BMI: 21.5–22.9), after adjusting for covariates. In contrast, high-normal weight (BMI: 23.0–24.9) and overweight (BMI: 25.0–26.9 and ≥ 27.0) were not associated with mortality. Relative to old-old (aged ≥ 75 years), the higher mortality risk associated with lower BMI (< 20) appeared to be more prominent among young-old (aged 60–74 years). A moderately increased mortality risk associated with low BMI (18.5–19.9) was identified among men but not among women. Conclusion: Among older Japanese, low BMI (< 20.0) was associated with higher mortality, while high BMI (≥ 27.0) was not. The increased mortality risk associated with low BMI is more apparent among young-old and men. These age and gender differences need to be considered in assessing healthy body weight in old age.